Phase I/II Clinical Trial of Autologous Activated Platelet-Rich Plasma (aaPRP) in the Treatment of Severe Coronavirus Disease 2019 (COVID-19) Patients - Karina Karina; Iis Rosliana; Imam Rosadi; Siti Sobariah; Louis Martin Christoffel; Rita Novariani; Siti Rosidah; Novy Fatkhurohman; Yuli Hertati; Nurlaela Puspitaningrum; Wismo Reja Subroto; Irsyah Afini; et al. (Hindawi Limited, 2021)
Background. The outbreak of Coronavirus Disease 2019 (COVID-19) has been increasing rapidly. This disease causes an increase in proinflammatory cytokine production that leads to cytokine storm or cytokine release syndrome (CRS). Autologous activated platelet-rich plasma (aaPRP) contains various types of growth factors and anti-inflammatory cytokines that may have the potential to suppress CRS. This study of phase I/II trial was aimed to evaluate the safety and efficacy of aaPRP to treat severe COVID-19 patients. Methods. A total of 10 severe COVID-19 patients from Koja Regional Public Hospital (Koja RPH) were admitted to the intensive care unit (ICU). All patients received aaPRP administration three times. Primary outcomes involving the duration of hospitalization, oxygen needs, time of recovery, and mortality were observed. Secondary outcomes involving C-reactive protein (CRP), neutrophil, lymphocyte, and lymphocyte-to-CRP (LCR) and neutrophil-lymphocyte ratio (NLR) were analyzed. Results. All patients were transferred to the ICU with a median duration of 9 days. All patients received oxygen at enrollment and nine of ten patients recovered from the ICU and transferred to the ward room. There was one patient who passed away in the ICU due to heart failure. The results of secondary outcomes showed that CRP value and lymphocytes counts were significantly decreased while neutrophils, LCR, and NLR were slightly increased after aaPRP administration. Conclusions. Our results of the phase I/II trial demonstrated that the use of aaPRP in severe COVID-19 patients was safe and not associated with serious adverse events, which showed that aaPRP was a promising adjunctive therapy for severe COVID-19 patients.